Pediatric Cough - Santosh Kumar Swain; Sampada Munjal; Suryakanta Pradhan (Apollo Medicine)
Cough in the pediatric age group is a common presenting complaint, and the etiology of the cough is often elusive. Although there is a high prevalence of cough in the pediatric age group, the subject is still poorly researched. The management of pediatric cough is different from adults. Cough in children causes a significant anxiety among parents and often leads to the use of inappropriate or unnecessary medications. Cough in the pediatric population is due to multiple underlying causes and the most common are allergy, infections, asthma, foreign body aspiration, and gastroesophageal reflux. Detailed history-taking and physical examination with chest X-ray and spirometry are often recommended for getting the diagnosis. Treatment is done according to the underlying disease, and there is poor evidence for prescribing medications only for symptomatic relief. This review article discusses the etiopathology and clinical characteristics of pediatric cough and its management.